(untitled) (Global Journal of Management and Business Research, 2019)
The fourth industrial revolution is currently changing the traditional manual system of operations. The dealing with manual issues or situations has changed into the use of technologies, computers, and machines. The organizations around the world are now more interested in investing in artificial intelligence to achieve bigger goals. Therefore, the present study intends to observe the artificial intelligence in human resources in Pakistan while comparing the performance with Australia. The study uses a questionnaire survey and applies multiple regression techniques for testing the hypotheses. The results indicate that the HR in companies of both countries implement AI. However, Australia is more efficient in successfully implementing AI in its enterprises’ HR.